Effects of bis-chelated copper in growth performance and gut health in broiler chickens subject to coccidiosis vaccination or coccidia challenge - Chen, Juxing; Yan, Frances; Kuttappan, Vivek A.; Wedekind, Karen; Vázquez-Añón, Mercedes; Hancock, Deana (Frontiers in Physiology, 2023)
Cu is widely used at high levels as growth promoter in poultry, the alternative source of Cu to replace high level of inorganic Cu at poultry farm remains to be determined. Three floor pen experiments were conducted to evaluate the effects of Cu methionine hydroxy-analogue chelate (Cu-MHAC, MINTREX®Cu, Novus International, Inc.) on growth performance and gut health in broilers in comparison to CuSO4 and/or tribasic copper chloride (TBCC). There were 3 treatments in experiment#1 (0, 30 and 75 ppm Cu-MHAC) and experiment#2 (15 and 30 ppm Cu-MHAC, and 125ppm CuSO4), and 4 treatments in experiment #3 (15 and 30 ppm Cu-MHAC, 125ppm CuSO4 and 125ppm TBCC) with 9 replicates pens of 10-13 birds in each treatment. The levels of other minerals were equal among all treatments within each experiment. All birds were orally gavaged with a coccidiosis vaccine at 1x recommended dose on d0 in experiment#1 and #2 and 10x recommended dose on d15 in experiment#3. Data were analyzed by one-way ANOVA, means were separated by Fisher’s protected LSD test. A P ≤ 0.05 was considered statistically different. In experiment #1, 30ppm and 75ppm Cu-MHAC improved FCR during grower phase, increased jejunal villus height and reduced jejunal crypt depth, 30ppm Cu-MHAC increased cecal Lactobacillus spp. abundance in 41d broilers. In experiment #2, compared to CuSO4, 15ppm Cu-MHAC increased cumulative performance index in 28d broilers, 15ppm and/or 30ppm Cu-MHAC improved gut morphometry, and 30ppm Cu-MHAC reduced the abundance of E.coli and Enterobacteriaceae in cecum in 43d broilers. In experiment #3, 15ppm and 30ppm Cu-MHAC improved FCR vs CuSO4 during starter phase, reduced the percentage of E. coli of total bacteria vs TBCC, 30ppm Cu-MHAC increased the percentages of Lactobacillus acidophilus, Lactobacillus spp. and Clostridium cluster XIVa of total bacteria vs both CuSO4 and TBCC in the cecum of 27d broilers. In summary, low doses of Cu-MHAC had comparable growth performance to high dose of TBCC and CuSO4 while improving gut microflora and gut morphometry in broilers subject to coccidiosis vaccination or coccidia challenge, indicating that low doses of bis-chelated Cu could be used as a complimentary strategy to help manage coccidiosis.